2004
DOI: 10.1159/000081626
|View full text |Cite
|
Sign up to set email alerts
|

Medical Consultation for Gastro-Oesophageal Reflux Symptoms: Reasons and Associated Factors

Abstract: Objectives: To evaluate the frequency of medical consultation for gastro-oesophageal reflux symptoms (GORS) and to ascertain reasons for consultation and associated factors. Methods: Telephone survey of 2,500 persons using a validated questionnaire. Data were analyzed using multiple logistic regression, in which the dependent variable was consultation for GORS and the independent variables were sociodemographic factors and the clinical characteristics of GORS. Results: Of those reporting GORS, 28% had consulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
2
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 24 publications
4
29
2
4
Order By: Relevance
“…Rey et al found that 42.6% of the individuals in their study sample who consulted a physician about GERD did so because of the severity of their symptoms. 22 In this study, both frequent symptoms (OR: 2.4; 95% CI: 1.6-3.5) and severe symptoms (OR: 2.4; 95% CI: 1.4-4.2) were independently associated with consultation. Total number of unique hits: n = 1166…”
Section: S Ys Te M a T I C Rev I E W: C Ons Ul T Atio N For G Erd Andmentioning
confidence: 48%
See 4 more Smart Citations
“…Rey et al found that 42.6% of the individuals in their study sample who consulted a physician about GERD did so because of the severity of their symptoms. 22 In this study, both frequent symptoms (OR: 2.4; 95% CI: 1.6-3.5) and severe symptoms (OR: 2.4; 95% CI: 1.4-4.2) were independently associated with consultation. Total number of unique hits: n = 1166…”
Section: S Ys Te M a T I C Rev I E W: C Ons Ul T Atio N For G Erd Andmentioning
confidence: 48%
“…19 Several other studies also reported consultation rates of about 30% per year. [20][21][22][23] A substantially higher consultation rate was found in a survey of 2000 individuals in Belgium. 24 Almost 30% of this survey population reported having symptoms of heartburn in the previous year, 56% of whom had consulted a physician about these symptoms.…”
Section: Most Patients With Gerd Do Not Consultmentioning
confidence: 91%
See 3 more Smart Citations